2010
DOI: 10.1353/pla.2010.0007
|View full text |Cite
|
Sign up to set email alerts
|

Academic/Research Librarians with Subject Doctorates: Experiences and Perceptions, 1965-2006

Abstract: The topic of academic/research librarians with subject doctorates remains largely unexplored. Based on survey data gathered from subject-doctorate holders (excluding those with doctorates in LIS) currently working in U.S. and Canadian academic/research libraries, this article extends the analysis published by the authors in the January 2008 issue of portal: Libraries and the Academy. While the first article featured quantitative analysis to highlight data and trends relating to these librarians over a 40-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Gilman and Lindquist evaluated the experiences and perceptions of academic librarians with subject doctorates. 4 They note a number of challenges for these individuals that include: perceptions of library colleagues, a tension between being both librarian and researcher, an undervaluing of the domain knowledge, and compensation. 5 These differences should be discussed with the candidates early in the search process in order to avoid wasting the time of the candidate and search committee.…”
Section: Interviewing Candidatesmentioning
confidence: 99%
“…Gilman and Lindquist evaluated the experiences and perceptions of academic librarians with subject doctorates. 4 They note a number of challenges for these individuals that include: perceptions of library colleagues, a tension between being both librarian and researcher, an undervaluing of the domain knowledge, and compensation. 5 These differences should be discussed with the candidates early in the search process in order to avoid wasting the time of the candidate and search committee.…”
Section: Interviewing Candidatesmentioning
confidence: 99%
“…While this route is not uncommon, there is not broad agreement on whether such education is necessary-or helpful-to the profession (Crowley, 2004;Ferguson, 2016;Mayer & Terrill, 2005). Researchers have demonstrated that those who had attained doctorates in subject areas felt this experience gave them credibility with faculty, expertise in their instructional disciplines, and deep research experience they could use to connect with students (Gilman & Lindquist, 2010). However, these librarians indicated that additional education was not the only route to gain advanced subject knowledge; they cited on-the-job experience and other learning undertakings as real difference-makers in developing their disciplinary understandings, not credentials or degrees.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies of students have shown a similar lack of awareness regarding librarian research (Fagan 2003). Gilman and Lindquist (2010) studied librarians with additional advanced subject degrees and found that even when librarians possessed these additional credentials they still felt their research skills were neither respected nor supported. Lack of support for librarian research is common; the collective agreements governing librarians often lack acceptable supports for librarian research (Babb 2017;Harrington and Gerolami 2014).…”
Section: Mots-clés : Bibliothécaires • Bibliothécaires En Tant Que Chmentioning
confidence: 99%